(untitled) - Addams, Charles; 1938-; Lloyd, Christopher; Huston, Anjelica; Sonnenfeld, Barry; Julia, Raul; 1912-1988. (Burbank, CA, 2017)
Long-lost Uncle Fester reappears in the lives of the ghoulish Addams family, headed by Morticia and Gomez; the adventures of the Addams family continue when Uncle Fester gets married to a murderous socialite, and Gomez and Morticia have another baby.
Keywords: Drama; Families; Addams family (Fictitious characters); Drama; Fantasy films; Comedy films